E0126 Study on anti-oxidative function of four kinds of schizandrae lignans. (17th November 2010) - Xin, Sun; Yu, Xie; Jianguang, Chen; Qi, Wang; Dan, Tian; Tan, Li
Abstract : Objective: To study the anti-oxidative function of schisandrin A (SinA), schisandrinB (SinB), schisandrolA (SolA) and schisandrin ester A (SesA). Methods: Using the method of the self oxidation method of pyrogallol, Fenton system. Results: The results shown that all of four kinds of schizandrae lignans have the inhibition function to Superoxide anion radical (O2 − ·), SinB had the highest inhibition rate which could arrive at 68.74%; They also had the same inhibition to hydroxyl radical (OH) and SinB have the best effect. Conclusions: schisandrin A (SinA), schisandrin B (SinB), schisandrolA (SolA) and schisandrin ester A (SesA) can be used as a natural anti-oxidation for human cardiovascular disease treatment and preventive health care.